2014
DOI: 10.1007/s00264-014-2622-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects on mobile polyethylene insert under highly demanding daily activities: stair climbing

Abstract: The results of this study demonstrated that the forces and motion sustained by the knee are highly activity-dependent. Moreover, this test confirmed that under more severe conditions, the material properties change according to a different wear mechanism and a decrease in crystallinity occurs. Loading characteristics for specific activities should be considered for the design of functional and robust TKRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Loading on knee joint primarily depends on the physical activity and body weight (BW). The high variability of loads, according to the anthropometric features specific to each subject, is observed from several studies [6,12,13,15,16]. These studies also point out that different people, with similar weight and height, show different load configurations due to their different ways to run specific movements.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Loading on knee joint primarily depends on the physical activity and body weight (BW). The high variability of loads, according to the anthropometric features specific to each subject, is observed from several studies [6,12,13,15,16]. These studies also point out that different people, with similar weight and height, show different load configurations due to their different ways to run specific movements.…”
Section: Discussionmentioning
confidence: 95%
“…A complex morphometric relation characterizes the knee and currently at the authors’ knowledge, there are no studies about the combined effect of patient weight and load applied on the knee. An in vivo performance of knee prostheses, according to the relation between patient body mass index (BMI) and load applied, showed high variability of load according to the anthropometric features specific to each subject [6,12,13,15,16]. These studies, performed on different people with similar weight and height, showed different load configurations due to the different ways in which anyone runs a specific movement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The so-called “patient’s daily activities” have to be considered as a worst-case scenario for testing, as well as for implant design. To cover these lacunae, based on previous studies [16,19,20], these experiences were translated to the hip simulator.…”
Section: Introductionmentioning
confidence: 99%